Faktor-Faktor Yang Berhubungan Dengan Kelelahan Kerja Pada Divisi Pengolahan Karyawan di Instalasi Gizi RSUD Mardi Waluyo Blitar - Viorel Sandha Resta; Nafilatul Fitri; Fresvian Jenrivo (Lembaga Pengembangan Kinerja Dosen, 2024)
Excessive physical, mental, or emotional exertion can lead to work fatigue, which is a decrease in almost all physical skills, including strength, speed, response time, coordination, balance, and decision making. Based on the previous pre-reset, it turned out that some employees at the Nutrition Installation of Mardi Waluyo Blitar Hospital were divided into three shifts where employees worked morning, afternoon, and night as a source of their complaints. This is possible because workers spend long hours and have a heavy workload, even though one person does many activities. This study aims to determine the relationship between fatigue factors in this example of work shifts and length of work at the Nutrition Installation of Mardi Waluyo Blitar Hospital with employee work fatigue. The method of this study is quantitative with a total sampling technique of total sampling on 32 respondents using Speareman Rank Collection analysis. The method of obtaining research data was carried out by field observation and filling out questionnaires. The results obtained were employees of the nutrition installation, especially in the processing division of Mardi Waluyo Blitar Hospital with the majority of female employees with a percentage (71.9%) or 23 out of 32 people. The majority of the age of the 32 samples observed was <25 years or (53.1%) The working mass of the majority of nutrition installation employees was <5 years with a percentage of (71.9%) or 23 people. Based on the results of statistical tests, there is a significant relationship between work shifts and work periods with complaints of work fatigue in nutrition installation employees, especially in the processing division of Mardi Waluyo Blitar Hospital. The conclusion that can be drawn is that there is a relationship between work shifts and work periods on work fatigue